Workforce Requirement Analysis Using Workload Analysis with a Full-Time Equivalent (FTE) Approach in the Planning & Control Division of PT PLN (Persero) Pusharlis UP2W VI - Anditta Aurellia Avisa; Moch Tutuk Safirin (Yayasan Kita Menulis, 2026)
This research was conducted at PT PLN (Persero) Pusharlis Unit Pelaksana Pemeliharaan Wilayah VI (UP2W VI), focusing on the Planning and Control Division. This study aims to analyze the suitability between workload and the number of employees and to determine the ideal workforce requirement to improve operational effectiveness. The method applied is workload analysis using the Full Time Equivalent (FTE) approach through the calculation of task completion time and annual effective working hours. The results indicate differences in workload levels among teams, where some teams experience overload conditions, while others operate under near-optimal workload conditions. The application of the Full Time Equivalent (FTE) method provides a quantitative overview of actual workload conditions and serves as a basis for determining and adjusting optimal workforce formation to support work efficiency in the Planning and Control Division of PT PLN (Persero) Pusharlis UP2W VI